A high temperature resistant toughening plugging agent for oil well cement

By adding components such as rare earth compounds, nano -carbonate, modified amorphous alloy fibers, and anti -high temperature modification starch to add compounds, nano -nanocarbonate, calcium carbonate, modified amorphous alloy fibers, and anti -high temperature modification starch, the traditional plugs are not durable and tough in high temperature and high pressure environment. The problem achieves high -strength, high toughness and stable well -solid effects.

CN118834047BActive Publication Date: 2025-01-28PANJIN HONGBO PETROLEUM TECH SERVICE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411322904.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-28
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing leak plugging agents for oil well cement are not durable and have poor toughness in high temperature and high pressure environments, making it difficult to meet the high requirements for oil and gas well cementing.

Method used

The use of an oil -well cement with anti -high temperature tougher plugging agent, which consists of G -class oil well cement, rare earth compounds, nano -carbonate, modified amorphous alloy fiber, anti -high temperature modified starch, water reduction agent, slowing agent and slowing agent, and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowing agent and slowdown agent and slowdown agent and slowdown. The auxiliary materials, through the preparation of modified amorphous alloy fibers and anti -high temperature modified starch, improve the high temperature stability and toughness of the leakage.

Benefits of technology

In high temperature environments, the leakage agent can quickly form a high -strength, high tough solidor, significantly improve the quality and pressure resistance of the well, extend the stability period of the cement ring, and meet the solids of the oil and gas well under the conditions of high temperature and high pressure conditions. The well needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005189591380000131
    Figure GDA0005189591380000131
  • Figure GDA0005189591380000141
    Figure GDA0005189591380000141
Patent Text Reader

Abstract

The invention discloses a high temperature resistant toughening plugging agent for oil well cement, belonging to the technical field of oil field chemistry. The high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 35-50 parts of G-grade oil well cement, 5-20 parts of rare earth compounds, 5-20 parts of nano calcium carbonate, 5-10 parts of modified amorphous alloy fibers, 5-10 parts of high temperature resistant modified starch, 1-5 parts of fluid loss reducer, 1-5 parts of retarder and 1-5 parts of auxiliary materials. The high temperature resistant toughening plugging agent for oil well cement of the present invention significantly improves the high temperature resistance of cement stone formed by the plugging agent and improves the toughness and impact resistance of cement stone by adding modified amorphous alloy fibers and high temperature resistant modified starch, and collocating rare earth compounds, nano calcium carbonate, fluid loss reducer, retarder and auxiliary materials through synergistic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oilfield chemistry, and in particular relates to a high temperature resistant toughening plugging agent for oil well cement. Background Art

[0002] With the continuous growth of global energy demand, the development of unconventional oil and gas resources has been continuously strengthened, especially the exploration and development of shale oil and gas resources, which has become an important direction in the energy field. However, these unconventional oil and gas resources are often located in environments with complex geological conditions and extreme changes in temperature and pressure, which poses unprecedented challenges to cementing materials and their performance. As the basic material in cementing operations of oil and gas wells, cementing cement mainly forms a strong cement ring, isolates formation fluids, and protects casing from corrosion and damage. However, with the increase in the depth of oil and gas wells and the complexity of geological conditions, traditional oil well cement materials have been difficult to meet the performance requirements under high temperature and high pressure environments. Especially with the widespread application of horizontal well technology and large-scale staged hydraulic fracturing technology, the rapid changes in temperature and pressure in the wellbore have put forward higher requirements on the elastic-plasticity, bending resistance, tensile strength and anti-channeling performance of cementing cement stone.

[0003] During the development of oil and water wells, production efficiency often decreases or even stops due to formation leakage, casing damage and other reasons. Traditional plugging methods mostly use inorganic gelling materials or thermosetting resins, which can solve some problems to a certain extent, but have limited effects under complex geological conditions such as high temperature, high pressure, and high mineralization. In addition, some methods such as replacement overhaul processes and lining with small diameter casings have long construction cycles and high costs, and are difficult to meet the needs of rapid resumption of production. Therefore, the development of a high-temperature resistant toughening plugging agent for oil well cement, which can quickly form a high-strength, high-toughness solidified body under high temperature environment, has become an important development direction of oil and water well plugging technology. Summary of the invention

[0004] The purpose of the present invention is to provide a high temperature resistant toughening plugging agent for oil well cement, which is used to solve the technical problems of the plugging agent for oil well cement in the prior art that is not resistant to high temperature and has poor toughness.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 35-50 parts of G-grade oil well cement, 5-20 parts of rare earth compounds, 5-20 parts of nano calcium carbonate, 5-10 parts of modified amorphous alloy fibers, 5-10 parts of high temperature resistant modified starch, 1-5 parts of fluid loss reducer, 1-5 parts of retarder and 1-5 parts of auxiliary materials.

[0007] The rare earth compound is one or more of yttrium oxide, lanthanum oxide and lanthanum boride; the fluid loss reducer is one or more of hydroxyethyl cellulose, carboxymethyl cellulose and polyvinyl alcohol; the retarder is one or more of borax, gluconate, wood calcium, wood sodium and citric acid; the auxiliary material is one or more of sulfonated tannin, sulfonated lignite and sulfonated phenolic resin SMP-2.

[0008] The preparation of modified amorphous alloy fiber includes the following steps:

[0009] (1) Pretreatment: The amorphous alloy fiber is immersed in isopropanol for ultrasonic oscillation, taken out and washed with deionized water, and placed in an oven for drying to obtain clean amorphous alloy fiber;

[0010] (2) Acid etching: The clean amorphous alloy fibers are immersed in a citric acid solution and placed at room temperature. After the reaction is completed, the fibers are cleaned under ultrasonic wave and then taken out and dried in a drying oven to obtain acid-etched amorphous alloy fibers.

[0011] (3) Coupling reaction: Ethanol, water and aminopropyltriethoxysilane solution are mixed evenly to obtain a mixed solution, and the pH is adjusted to carry out a hydrolysis reaction. After the reaction is completed, nano-Al2O3 is added to the mixed solution and stirred to obtain a nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber is immersed in a NaOH solution, and after the reaction is completed, it is added to the nano-Al2O3 mixed solution and stirred. After the reaction is completed, it is taken out and dried in a drying oven to obtain the modified amorphous alloy fiber.

[0012] Furthermore, in step (1), the ultrasonic oscillation is performed for 10 to 15 minutes, the oven drying temperature is 70 to 80° C., and the drying time is 4 to 6 hours; in step (2), the concentration of the citric acid solution is 8 to 10 mol / L, the mixture is placed at room temperature for 6 to 10 hours, and the mixture is cleaned for 10 to 15 minutes under an ultrasonic wave of 80 to 100 kHz, the temperature of the drying oven is 70 to 80° C., and the drying time is 4 to 6 hours; in step (3), the volume ratio of ethanol to water is (8 to 10): 1, the final mass concentration of aminopropyltriethoxysilane is 10%, the pH is adjusted to 5 to 6 with Tris-HCl buffer, the hydrolysis time is 2 to 4 hours, the mass concentration of the nano-Al2O3 mixed solution is 2 to 3%, the concentration of the NaOH solution is 0.3 to 0.6 M, the mixture is immersed for 0.5 to 2 hours, the temperature of the drying oven is 70 to 80° C., and the drying time is 4 to 6 hours.

[0013] The preparation method of high temperature resistant modified starch comprises the following steps:

[0014] S1. Raw material preparation: sieve corn starch to obtain uniform starch granules;

[0015] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, and put them into a constant temperature dryer to preliminarily dry the wet starch to obtain slightly wet starch granules;

[0016] S3, high temperature treatment: putting slightly wet starch granules into a high temperature furnace, and obtaining a high temperature resistant modified starch pre-finished product after completion;

[0017] S4, cooling and drying: After the high temperature treatment, the crucible is taken out of the high temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven to obtain a high temperature resistant modified starch.

[0018] Furthermore, the mesh number of the sieve in S1 is 80-100; the moisture content of the slightly moist starch granules in S2 is controlled at 10-20%, wherein the moisture content is determined by the constant weight drying method, a sample of slightly moist starch granules is taken, dried to constant weight in an oven at 105°C, and the moisture content is calculated; the temperature of the high-temperature furnace in S3 is 200°C, the heating time is 2h, the drying oven temperature is set to 80-90°C, and the drying time is 4-6h, to obtain high-temperature resistant modified starch.

[0019] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0020] 1. The high temperature toughening plugging agent for oil well cement of the present invention is prepared by adding modified amorphous alloy fiber and high temperature modified starch, and collocating rare earth compounds, nano calcium carbonate, fluid loss reducer, retarder and auxiliary materials on the basis of the prior art. The rare earth compounds and nano calcium carbonate have good high temperature stability. The addition of fluid loss reducer significantly reduces the water loss of cement slurry, improves the stability of cement slurry and cementing quality, especially under high temperature conditions, maintains the fluidity and plasticity of cement slurry, prevents premature solidification and performance degradation of cement ring, and the reasonable proportion of retarder ensures that cement slurry has suitable initial setting time at high temperature, avoids premature solidification, and provides sufficient time for cementing operation, thereby ensuring cementing quality. In addition, the addition of auxiliary materials further improves the compressive strength of cement stone formed by the plugging agent through synergistic effect, and improves the toughness and impact resistance of cement stone.

[0021] 2. During the preparation of the modified amorphous alloy fiber of the present invention, acid etching is used to not only increase the specific surface area of ​​the amorphous alloy fiber and improve the overall mechanical properties of the cement stone, but also to remove part of the oxide layer on the surface of the amorphous alloy fiber, thereby increasing the binding sites between the fiber and nano-Al2O3. The attachment of nano-Al2O3 in the coupling reaction further improves the strength and toughness of the amorphous alloy fiber, so that it can still maintain good mechanical properties under high temperature environment, and effectively prevent the plugging agent from cracking or failing under high temperature. Nano-Al2O3, as a material with high melting point and high thermal stability, can significantly improve the high temperature resistance of the fiber. At the same time, the use of the coupling agent also enhances the interfacial bonding between the fiber and the cement matrix, further improving the stability of the plugging agent at high temperature.

[0022] 3. The preparation of the high temperature resistant modified starch of the present invention uses a natural polymer material - starch, which is widely available and renewable, and is environmentally friendly. The starch undergoes partial carbonization and dehydration reaction through high temperature treatment, forming a more stable high temperature resistant structure. This structure enables the starch to maintain a certain viscosity and fluidity under high temperature environment, thereby effectively preventing the plugging agent from hardening or losing viscosity prematurely under high temperature. After improving its high temperature resistance through modification treatment, it can replace part of the traditional organic thickener, thereby reducing the impact and dependence on the environment. In addition, the entire preparation process is relatively simple and environmentally friendly, meeting the needs of green oil field development. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1

[0025] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 50 g of G-grade oil well cement, 5 g of rare earth compound, 5 g of nano calcium carbonate, 5 g of modified amorphous alloy fiber, 5 g of high temperature resistant modified starch, 1 g of fluid loss reducing agent, 1 g of retarder and 1 g of auxiliary material.

[0026] The rare earth compound is yttrium oxide; the fluid loss reducer is an equal mixture of hydroxyethyl cellulose and carboxymethyl cellulose; the retarder is an equal mixture of borax and citric acid; and the auxiliary material is sulfonated tannin.

[0027] Specifically, the preparation of the modified amorphous alloy fiber includes the following steps:

[0028] (1) Pretreatment: The amorphous alloy fiber was immersed in isopropanol and subjected to ultrasonic oscillation for 10 min. After being taken out, it was washed with deionized water and placed in an oven for drying at a temperature of 70°C for a drying time of 6 h to obtain clean amorphous alloy fibers.

[0029] (2) Acid etching: The clean amorphous alloy fiber was immersed in a solution of 8 mol / L citric acid and placed at room temperature for 6 h. After the reaction was completed, the fiber was cleaned under 80 kHz ultrasonic wave for 10 min, and then taken out and dried in a drying oven at 70 ° C for 4 h to obtain an acid-etched amorphous alloy fiber.

[0030] (3) Coupling reaction: 120 mL of ethanol, 15 mL of water and 13.5 g of aminopropyltriethoxysilane solution were mixed evenly to obtain a mixed solution, and the pH was adjusted to 5 with Tris-HCl buffer for hydrolysis reaction. The hydrolysis time was 2 h. After the hydrolysis was completed, nano-Al2O3 was added to the mixed solution and stirred to obtain a 2% nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber was immersed in a 0.3 M NaOH solution for 0.5 h. After the reaction was completed, it was added to the nano-Al2O3 mixed solution and stirred. After the reaction was completed, it was taken out and dried in a drying oven at a temperature of 70°C for 4 h to obtain a modified amorphous alloy fiber.

[0031] The preparation method of high temperature resistant modified starch comprises the following steps:

[0032] S1. Raw material preparation: pass corn starch through an 80-mesh sieve to obtain uniform starch granules;

[0033] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, put into a constant temperature dryer to preliminarily dry the wet starch, and use a constant weight drying method to determine the moisture content to obtain 10% slightly wet starch granules;

[0034] S3, high temperature treatment: 10% slightly wet starch granules are placed in a 200°C high temperature furnace for 2 hours, after which a high temperature resistant modified starch pre-finished product is obtained;

[0035] S4, cooling and drying: After the high-temperature treatment, the crucible is taken out of the high-temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven. The oven temperature is set to 80° C. and the drying time is 4 hours to obtain high-temperature resistant modified starch.

[0036] Embodiment 2

[0037] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 45 g of G-grade oil well cement, 10 g of rare earth compound, 10 g of nano calcium carbonate, 7 g of modified amorphous alloy fiber, 7 g of high temperature resistant modified starch, 2 g of fluid loss reducing agent, 2 g of retarder and 2 g of auxiliary material.

[0038] The rare earth compound is lanthanum oxide; the fluid loss reducer is polyvinyl alcohol; the retarder is an equal mixture of borax and gluconate; and the auxiliary material is an equal mixture of sulfonated tannin and sulfonated phenolic resin SMP-2.

[0039] The preparation of modified amorphous alloy fiber includes the following steps:

[0040] (1) Pretreatment: The amorphous alloy fiber was immersed in isopropanol and subjected to ultrasonic oscillation for 12 min. After being taken out, it was washed with deionized water and placed in an oven for drying at a temperature of 72°C for a drying time of 4.5 h to obtain clean amorphous alloy fibers.

[0041] (2) Acid etching: The clean amorphous alloy fiber is immersed in a solution of 8 mol / L citric acid and placed at room temperature for 6 to 10 hours. After the reaction is completed, it is cleaned under 100 kHz ultrasonic wave for 10 minutes, taken out and dried in a drying oven at a drying temperature of 70°C for 4 hours to obtain an acid-etched amorphous alloy fiber;

[0042] (3) Coupling reaction: 120 mL of ethanol, 15 mL of water and 13.5 g of aminopropyltriethoxysilane solution were mixed evenly to obtain a mixed solution, and the pH was adjusted to 5 with Tris-HCl buffer for hydrolysis reaction. The hydrolysis time was 2 h. After the hydrolysis was completed, nano-Al2O3 was added to the mixed solution and stirred to obtain a 2.5% nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber was immersed in a 0.3 M NaOH solution for 0.5 h. After the reaction was completed, the fiber was added to the nano-Al2O3 mixed solution and stirred. After the reaction was completed, the fiber was taken out and dried in a drying oven at a temperature of 70-80°C for a drying time of 4-6 h to obtain a modified amorphous alloy fiber.

[0043] Specifically, the preparation method of high temperature resistant modified starch comprises the following steps:

[0044] S1. Raw material preparation: pass corn starch through a 90-mesh sieve to obtain uniform starch granules;

[0045] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, put into a constant temperature dryer to preliminarily dry the wet starch, and use a constant weight drying method to determine the moisture content to obtain 10% slightly wet starch granules;

[0046] S3, high temperature treatment: 10% slightly wet starch granules are placed in a 200°C high temperature furnace for 2 hours, after which a high temperature resistant modified starch pre-finished product is obtained;

[0047] S4, cooling and drying: After the high temperature treatment, the crucible is taken out of the high temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven. The oven temperature is set to 80° C. and the drying time is 4 to 6 hours to obtain high temperature resistant modified starch.

[0048] Embodiment 3

[0049] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 48g of G-grade oil well cement, 5g of rare earth compound, 10g of nano calcium carbonate, 7g of modified amorphous alloy fiber, 6g of high temperature resistant modified starch, 2g of fluid loss reducing agent, 2g of retarder and 1.5g of auxiliary materials.

[0050] The rare earth compound is lanthanum boride; the fluid loss reducer is hydroxyethyl cellulose; the retarder is an equal mixture of wood calcium and gluconate; and the auxiliary material is sulfonated lignite.

[0051] Specifically, the preparation of the modified amorphous alloy fiber includes the following steps:

[0052] (1) Pretreatment: The amorphous alloy fiber was immersed in isopropanol and subjected to ultrasonic oscillation for 13 min. After being taken out, it was washed with deionized water and placed in an oven for drying at a temperature of 75°C for a drying time of 5 h to obtain clean amorphous alloy fibers.

[0053] (2) Acid etching: The clean amorphous alloy fiber was immersed in a solution of 8.5 mol / L citric acid and placed at room temperature for 7 h. After the reaction was completed, the fiber was cleaned under 100 kHz ultrasonic wave for 12 min, and then taken out and dried in a drying oven at a drying temperature of 70°C for 4 h to obtain an acid-etched amorphous alloy fiber.

[0054] (3) Coupling reaction: 130 mL of ethanol, 15 mL of water and 14.5 g of aminopropyltriethoxysilane solution were mixed evenly to obtain a mixed solution, and the pH was adjusted to 5.5 with Tris-HCl buffer for hydrolysis reaction. The hydrolysis time was 3 h. After the hydrolysis was completed, nano-Al2O3 was added to the mixed solution and stirred to obtain a 2.8% nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber was immersed in 0.4 M NaOH solution for 1 h. After the reaction was completed, it was added to the nano-Al2O3 mixed solution and stirred. After the reaction was completed, it was taken out and dried in a drying oven at a temperature of 72°C for 4 h to obtain a modified amorphous alloy fiber.

[0055] Specifically, the preparation method of high temperature resistant modified starch comprises the following steps:

[0056] S1. Raw material preparation: pass corn starch through a 100-mesh sieve to obtain uniform starch granules;

[0057] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, put into a constant temperature dryer to preliminarily dry the wet starch, and use a constant weight drying method to determine the moisture content to obtain 13% slightly wet starch granules;

[0058] S3, high temperature treatment: 13% slightly wet starch granules are placed in a 200°C high temperature furnace for 2 hours, after which a high temperature resistant modified starch pre-finished product is obtained;

[0059] S4, cooling and drying: After the high-temperature treatment, the crucible is taken out of the high-temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven. The oven temperature is set to 85° C. and the drying time is 6 hours to obtain high-temperature resistant modified starch.

[0060] Embodiment 4

[0061] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 50 g of G-grade oil well cement, 8 g of rare earth compound, 12 g of nano calcium carbonate, 8 g of modified amorphous alloy fiber, 8 g of high temperature resistant modified starch, 2.2 g of fluid loss reducer, 2.5 g of retarder and 3 g of auxiliary material.

[0062] The rare earth compound is lanthanum boride; the fluid loss reducer is carboxymethyl cellulose; the retarder is an equal mixture of sodium lignin and borax; and the auxiliary material is an equal mixture of sulfonated tannin and sulfonated lignite.

[0063] The preparation of modified amorphous alloy fiber includes the following steps:

[0064] (1) Pretreatment: The amorphous alloy fiber was immersed in isopropanol and subjected to ultrasonic oscillation for 15 min. After being taken out, it was washed with deionized water and placed in an oven for drying at a temperature of 75°C for a drying time of 5 h to obtain clean amorphous alloy fibers.

[0065] (2) Acid etching: The clean amorphous alloy fiber was immersed in a 9 mol / L citric acid solution and placed at room temperature for 8 h. After the reaction was completed, the fiber was cleaned under 90 kHz ultrasonic wave for 10 min, and then taken out and dried in a drying oven at 70 ° C for 6 h to obtain an acid-etched amorphous alloy fiber.

[0066] (3) Coupling reaction: 140 mL of ethanol, 15 mL of water and 15.5 g of aminopropyltriethoxysilane solution were mixed evenly to obtain a mixed solution, and the pH was adjusted to 6 with Tris-HCl buffer for hydrolysis reaction. The hydrolysis time was 3 h. After the hydrolysis was completed, nano-Al2O3 was added to the mixed solution and stirred to obtain a 2.9% nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber was immersed in 0.4 M NaOH solution for 1 h. After the reaction was completed, it was added to the nano-Al2O3 mixed solution and stirred. After the reaction was completed, it was taken out and dried in a drying oven at a temperature of 75°C for 5 h to obtain a modified amorphous alloy fiber.

[0067] The preparation method of high temperature resistant modified starch comprises the following steps:

[0068] S1. Raw material preparation: pass corn starch through a 100-mesh sieve to obtain uniform starch granules;

[0069] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, put into a constant temperature dryer to preliminarily dry the wet starch, and use a constant weight drying method to determine the moisture content to obtain 17% slightly wet starch granules;

[0070] S3, high temperature treatment: put 17% slightly wet starch granules into a 200°C high temperature furnace for 2 hours, and obtain a high temperature resistant modified starch pre-finished product after heating;

[0071] S4, cooling and drying: After the high-temperature treatment, the crucible is taken out of the high-temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven. The oven temperature is set to 85° C. and the drying time is 6 hours to obtain high-temperature resistant modified starch.

[0072] Embodiment 5

[0073] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 35 g of G-grade oil well cement, 20 g of rare earth compound, 15 g of nano calcium carbonate, 9 g of modified amorphous alloy fiber, 9 g of high temperature resistant modified starch, 3 g of fluid loss reducing agent, 2 g of retarder and 2 g of auxiliary material.

[0074] The rare earth compound is an equal mixture of lanthanum oxide and lanthanum boride; the fluid loss reducer is an equal mixture of hydroxyethyl cellulose, carboxymethyl cellulose and polyvinyl alcohol; the retarder is an equal mixture of sodium lignin and citric acid; and the auxiliary material is an equal mixture of sulfonated tannin and sulfonated lignite.

[0075] Specifically, the preparation of the modified amorphous alloy fiber includes the following steps:

[0076] (1) Pretreatment: The amorphous alloy fiber was immersed in isopropanol and subjected to ultrasonic oscillation for 15 min. After being taken out, it was washed with deionized water and placed in an oven for drying at a temperature of 80°C for a drying time of 6 h to obtain clean amorphous alloy fibers.

[0077] (2) Acid etching: The clean amorphous alloy fiber was immersed in a 10 mol / L citric acid solution and placed at room temperature for 10 h. After the reaction was completed, it was cleaned under 100 kHz ultrasonic wave for 15 min, and then taken out and dried in a drying oven at a drying temperature of 78 ° C and a drying time of 5 h to obtain an acid-etched amorphous alloy fiber;

[0078] (3) Coupling reaction: 120 mL of ethanol, 15 mL of water and 13.5 g of aminopropyltriethoxysilane solution were mixed evenly to obtain a mixed solution, and the pH was adjusted to 5.8 with Tris-HCl buffer for hydrolysis reaction. The hydrolysis time was 4 h. After the hydrolysis was completed, nano-Al2O3 was added to the mixed solution and stirred to obtain a 3% nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber was immersed in 0.5 M NaOH solution for 1.5 h. After the reaction was completed, it was added to the nano-Al2O3 mixed solution and stirred. After the reaction was completed, it was taken out and dried in a drying oven at a temperature of 80°C for 6 h to obtain a modified amorphous alloy fiber.

[0079] Specifically, the preparation method of high temperature resistant modified starch comprises the following steps:

[0080] S1. Raw material preparation: pass corn starch through an 80-mesh sieve to obtain uniform starch granules;

[0081] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, put into a constant temperature dryer to preliminarily dry the wet starch, and use a constant weight drying method to determine the moisture content to obtain 19% slightly wet starch granules;

[0082] S3, high temperature treatment: put the 19% slightly wet starch granules into a 200°C high temperature furnace for 2 hours, and obtain a high temperature resistant modified starch pre-finished product after heating;

[0083] S4, cooling and drying: After the high-temperature treatment, the crucible is taken out of the high-temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven. The oven temperature is set to 80-90° C. and the drying time is 4-6 hours to obtain high-temperature resistant modified starch.

[0084] Embodiment 6

[0085] A high temperature resistant toughening plugging agent for oil well cement comprises the following components in parts by weight: 40 g of G-grade oil well cement, 20 g of rare earth compound, 20 g of nano calcium carbonate, 10 g of modified amorphous alloy fiber, 10 g of high temperature resistant modified starch, 5 g of fluid loss reducing agent, 5 g of retarder and 5 g of auxiliary materials.

[0086] The rare earth compound is an equal mixture of yttrium oxide and lanthanum oxide; the fluid loss reducer is an equal mixture of carboxymethyl cellulose and polyvinyl alcohol; the retarder is an equal mixture of borax, gluconate, calcium lignin, sodium lignin and citric acid; and the auxiliary material is an equal mixture of sulfonated tannin and sulfonated phenolic resin SMP-2.

[0087] Specifically, the preparation of the modified amorphous alloy fiber includes the following steps:

[0088] (1) Pretreatment: The amorphous alloy fiber was immersed in isopropanol and subjected to ultrasonic oscillation for 15 min. After being taken out, it was washed with deionized water and placed in an oven for drying at a temperature of 80°C for a drying time of 6 h to obtain clean amorphous alloy fibers.

[0089] (2) Acid etching: The clean amorphous alloy fiber was immersed in a 10 mol / L citric acid solution and placed at room temperature for 10 h. After the reaction was completed, the fiber was cleaned under 100 kHz ultrasonic wave for 15 min, and then taken out and dried in a drying oven at a drying temperature of 80°C for 5 h to obtain an acid-etched amorphous alloy fiber.

[0090] (3) Coupling reaction: 150 mL of ethanol, 15 mL of water and 16.5 g of aminopropyltriethoxysilane solution were mixed evenly to obtain a mixed solution, and the pH was adjusted to 6 with Tris-HCl buffer for hydrolysis reaction. The hydrolysis time was 4 h. After the hydrolysis was completed, nano-Al2O3 was added to the mixed solution and stirred to obtain a 3% nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber was immersed in a 0.6 M NaOH solution for 2 h. After the reaction was completed, it was added to the nano-Al2O3 mixed solution and stirred. After the reaction was completed, it was taken out and dried in a drying oven at a temperature of 80°C for 6 h to obtain a modified amorphous alloy fiber.

[0091] Specifically, the preparation method of high temperature resistant modified starch comprises the following steps:

[0092] S1. Raw material preparation: pass corn starch through a 100-mesh sieve to obtain uniform starch granules;

[0093] S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, put into a constant temperature dryer to preliminarily dry the wet starch, and use a constant weight drying method to determine the moisture content to obtain 20% slightly wet starch granules;

[0094] S3, high temperature treatment: 20% slightly wet starch granules are placed in a 200°C high temperature furnace for 2 hours, after which a high temperature resistant modified starch pre-finished product is obtained;

[0095] S4, cooling and drying: After the high temperature treatment, the crucible is taken out of the high temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven. The oven temperature is set to 90° C. and the drying time is 6 hours to obtain high temperature resistant modified starch.

[0096] Comparative Example 1

[0097] Comparative Example 1 Compared with Example 6, in Comparative Example 1, no modified amorphous alloy fiber is added to a high temperature resistant toughening plugging agent for oil well cement, and other conditions remain unchanged.

[0098] Comparative Example 2

[0099] Comparative Example 2 Compared with Example 6, in Comparative Example 2, no high-temperature resistant modified starch is added to the high-temperature resistant toughening plugging agent for oil well cement, and other conditions remain unchanged.

[0100] Comparative Example 3

[0101] Comparative Example 3 Compared with Example 6, in Comparative Example 3, no rare earth compound is added to the high temperature resistant toughening plugging agent for oil well cement, and other conditions remain unchanged.

[0102] Comparative Example 4

[0103] Comparative Example 4 Compared with Example 6, in Comparative Example 4, no auxiliary materials are added to the high-temperature resistant toughening plugging agent for oil well cement, and other conditions remain unchanged.

[0104] Experimental example

[0105] The performance of the high temperature resistant toughening plugging agent for oil well cement of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4 was measured.

[0106] 1. Determination of high temperature aging resistance

[0107] First, 3 portions of 5g of plugging agent were weighed for each embodiment and comparative example, and were respectively loaded into 3 aging tanks. The aging tanks were filled with drilling fluid to isolate oxygen in the air, and then sealed and placed in a roller heating furnace at 200°C for aging for 24 hours, and the aging tanks were taken out; then, after the aging tanks were cooled to room temperature, the plugging agent was taken out, washed, dried, and weighed, and the average of the 3 weighing results was taken and recorded as M. t ; Finally, M t Substitute into the mass loss rate formula to calculate the mass loss rate K of the plugging agent before and after aging. The calculation formula of mass loss rate K is: K = 100*(5-M t ) / 5, where M tis the mass of plugging agent after high temperature aging. The calculation results are shown in Table 1.

[0108] Table 1

[0109]

[0110]

[0111] From the calculation results in Table 1, it can be seen that the high temperature toughening plugging agent for oil well cement in Examples 1 to 6 of the present invention has high high temperature aging resistance, and the mass loss rate is low after high temperature aging treatment. From the comparison between Examples 1 to 6 and Comparative Examples 1 to 4, it can be seen that after adding modified amorphous alloy fiber, high temperature modified starch, rare earth compound and auxiliary materials, the mass loss rate is small under high temperature conditions, and it has excellent high temperature aging resistance.

[0112] 2. Determination of compressive performance

[0113] The high temperature resistant toughening plugging agent for oil well cement of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4 was stirred evenly, poured into a 5cm×5cm×5cm sealed mold, placed in an oil bath, and cured at 130°C and 150°C for 72h respectively. The compressive strength after curing was measured by a compressive strength tester. The measurement results are shown in Table 2.

[0114] Table 2

[0115] Group No. 130℃ compressive strength / MPa 150℃ compressive strength / MPa Embodiment 1 42.21 40.14 Embodiment 2 43.16 41.05 Embodiment 3 43.24 41.24 Embodiment 4 43.26 41.30 Embodiment 5 43.79 41.57 Embodiment 6 43.85 41.68 Comparative Example 1 20.02 18.04 Comparative Example 2 21.56 19.50 Comparative Example 3 22.15 20.09 Comparative Example 4 22.43 20.14

[0116] From the measurement results in Table 2, it can be seen that by comparing Examples 1 to 6 with Comparative Examples 1 to 4, it can be seen that after adding modified amorphous alloy fiber, high temperature resistant modified starch, rare earth compound and auxiliary materials, the compressive performance is enhanced under high temperature conditions, and has excellent compressive performance.

[0117] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0118] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high temperature resistant toughening plugging agent for oil well cement, characterized in that: The invention comprises the following components in parts by weight: 35-50 parts of G-grade oil well cement, 5-20 parts of rare earth compounds, 5-20 parts of nano calcium carbonate, 5-10 parts of modified amorphous alloy fibers, 5-10 parts of high temperature resistant modified starch, 1-5 parts of fluid loss reducing agent, 1-5 parts of retarder and 1-5 parts of auxiliary materials; The preparation of the modified amorphous alloy fiber comprises the following steps: (1) Pretreatment: The amorphous alloy fiber is immersed in isopropanol for ultrasonic oscillation, taken out and washed with deionized water, and placed in an oven for drying to obtain clean amorphous alloy fiber; (2) Acid etching: The clean amorphous alloy fibers are immersed in a citric acid solution and placed at room temperature. After the reaction is completed, the fibers are cleaned under ultrasonic wave and then taken out and dried in a drying oven to obtain acid-etched amorphous alloy fibers. (3) Coupling reaction: ethanol, water and aminopropyl triethoxysilane solution are mixed evenly to obtain a mixed solution, and the pH is adjusted to perform a hydrolysis reaction. After the reaction is completed, nano-Al2O3 is added to the mixed solution and stirred to obtain a nano-Al2O3 mixed solution. At the same time, the acid-etched amorphous alloy fiber is immersed in a NaOH solution, and after the reaction is completed, it is added to the nano-Al2O3 mixed solution and stirred. After the reaction is completed, it is taken out and dried in a drying oven to obtain a modified amorphous alloy fiber; The preparation method of the high temperature resistant modified starch comprises the following steps: S1. Raw material preparation: sieve corn starch to obtain uniform starch granules; S2. Moisture adjustment: Mix the uniform starch granules with deionized water, stir evenly, and put them into a constant temperature dryer to preliminarily dry the wet starch to obtain slightly wet starch granules; S3, high temperature treatment: putting slightly wet starch granules into a high temperature furnace, and obtaining a high temperature resistant modified starch pre-finished product after completion; S4, cooling and drying: After the high temperature treatment, the crucible is taken out of the high temperature furnace and placed in a room temperature environment for natural cooling. After cooling, it is dried in an oven to obtain a high temperature resistant modified starch.

2. The high temperature resistant toughening plugging agent for oil well cement according to claim 1, characterized in that: The rare earth compound is one or more of yttrium oxide, lanthanum oxide and lanthanum boride; the fluid loss reducer is one or more of hydroxyethyl cellulose, carboxymethyl cellulose and polyvinyl alcohol; the retarder is one or more of borax, gluconate, wood calcium, wood sodium and citric acid; the auxiliary material is one or more of sulfonated tannin, sulfonated lignite and sulfonated phenolic resin SMP-2.

3. The high temperature resistant toughening plugging agent for oil well cement according to claim 1, characterized in that: In step (1), the ultrasonic oscillation is performed for 10 to 15 minutes, the oven drying temperature is 70 to 80° C., and the drying time is 4 to 6 hours. In step (2), the concentration of the citric acid solution is 8 to 10 mol / L, the solution is placed at room temperature for 6 to 10 hours, and the solution is cleaned at an ultrasonic wave of 80 to 100 kHz for 10 to 15 minutes. The temperature of the drying oven is 70 to 80° C. and the drying time is 4 to 6 hours.

4. The high temperature resistant toughening plugging agent for oil well cement according to claim 1, characterized in that: In step (3), the volume ratio of ethanol to water is (8-10):1, the final mass concentration of aminopropyltriethoxysilane added is 10%, the pH is adjusted to 5-6 with Tris-HCl buffer, the hydrolysis time is 2-4 hours, the mass concentration of the nano-Al2O3 mixed solution is 2-3%, the concentration of the NaOH solution is 0.3-0.6M, the soaking is 0.5-2 hours, the temperature of the drying oven is 70-80°C, and the drying time is 4-6 hours.

5. The high temperature resistant toughening plugging agent for oil well cement according to claim 1, characterized in that: The mesh number of S1 medium mesh screen is 80-100.

6. The high temperature resistant toughening plugging agent for oil well cement according to claim 1, characterized in that: The moisture content of the slightly moist starch granules in S2 is controlled at 10-20%.

7. The high temperature resistant toughening plugging agent for oil well cement according to claim 1, characterized in that: The temperature of the high temperature furnace in S3 is 200°C, the heating time is 2h, the temperature of the drying oven is set to 80-90°C, and the drying time is 4-6h to obtain high temperature resistant modified starch.

Citation Information

Patent Citations

  • Environment-friendly blocking agent for drilling fluid and preparation method thereof

    CN109735311A

  • Surface-modified amorphous fiber reinforced concrete, and preparation method and coastal defense application thereof

    CN111217564A

  • Ultramicro channeling-sealing and plugging agent, and preparation method and application thereof

    CN111560240A